SEED GERMINATION OF NERIUM OLEANDER L. 'HARDY RED' VARIETIES IN LABORATORY CONDITIONS (Scientific journal of the Fergana State University, 2024)
The article presents the results of the study of the germination of seeds of the introduced variety of Nerium oleander 'Hardy red' in the conditions of the Karshi oasis. Scientific experiments were carried out on the seeds of the 1st and 2nd year of the 2023-2024 harvest from a plant grown in the Karshi oasis. Studies have shown that the optimal temperature for the seeds of the Nerium oleander 'Hardy red' variety is 24-25°C. According to the results of the experiments, the germination of seeds of the Nerium oleander 'Hardy red' variety in laboratory conditions was 84% ​​for 2-year-old seeds and 98% for 1-year-old seeds. This result showed that the seeds obtained by plants in the conditions of the Karshi oasis had a high germination from the first year, and this high germination allowed the plant to adapt to these conditions.